2020
DOI: 10.1016/j.echo.2019.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Association of Left Ventricular Ejection Fraction with Mortality and Hospitalizations

Abstract: Background: Although echocardiography is widely used to measure left ventricular ejection fraction (LVEF), its prognostic value has not been demonstrated in a broad range of patients including those acutely hospitalized for cardiac or noncardiac causes. We determined whether greater degrees of left ventricular systolic dysfunction were associated with progressively increasing risks of death or cardiovascular hospitalizations among patients in hospital or outpatient settings. Methods: A total of 27,323 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…This critical gap in the literature is particularly evident when considering the predominance of men and a lack of sex-specific data. [8][9][10] Previously, the National Echocardiography Database Australia (NEDA) 11 has identified clinically important thresholds of mortality risk in respect to pulmonary hypertension, 12 aortic stenosis 13 and, most recently, diastolic dysfunction. 14 Applying an expanded version of this unique resource, the primary aim of this study was to generate sex-specific data on the distribution of routinely observed LVEF levels and then examine their relationship to the risk of subsequent mortality.…”
Section: Introductionmentioning
confidence: 99%
“…This critical gap in the literature is particularly evident when considering the predominance of men and a lack of sex-specific data. [8][9][10] Previously, the National Echocardiography Database Australia (NEDA) 11 has identified clinically important thresholds of mortality risk in respect to pulmonary hypertension, 12 aortic stenosis 13 and, most recently, diastolic dysfunction. 14 Applying an expanded version of this unique resource, the primary aim of this study was to generate sex-specific data on the distribution of routinely observed LVEF levels and then examine their relationship to the risk of subsequent mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal pharmacological and non-pharmacological decisions, mostly based on LVEF, have improved DCM prognosis drastically 16 . Major arrhythmogenic episodes, sudden death events and mortality are related to DCM with lower EF ≤ 35% 7 . The impact of stratifying the severity of systolic impairment is crucial in DCM as shown 6 , 7 , 17 , but access to the EF has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Major arrhythmogenic episodes, sudden death events and mortality are related to DCM with lower EF ≤ 35% 7 . The impact of stratifying the severity of systolic impairment is crucial in DCM as shown 6 , 7 , 17 , but access to the EF has several limitations. The need for expert professionals, intra- and inter-observational differences or time-consuming imaging techniques in transthoracic echocardiography or cardiac magnetic resonance, as well as inaccessible or excessive radiation imaging techniques, make it difficult to monitor the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As recently as only a few weeks ago, we have learned that the left ventricular ejection fraction (LVEF), a marker, though controversial, of left ventricular systolic function, may indeed predict mortality in a wide variety of population with diverse pathologies, cardiac and non‐cardiac 5 . The argument on the merit of LVEF as a measure of systolic function has grown over the years, and today, we all agree that left ventricular global longitudinal strain (LVGLS) with or without LVEF remains the marker of choice to assess LV systolic function in a wide variety of cardiac illnesses 6 .…”
Section: Why Diastole and Why Does It Matter? Because This Needs Thrmentioning
confidence: 99%